1986
DOI: 10.1103/physrevb.34.1956
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Bi observed with point contacts

Abstract: Point contacts~ith the semimetal Bi sho~a nonlinear structure in the current-voltage characteristics at liquid-helium temperatures.Because of the dependence on temperature and magnetic field this anomalous structure is ascribed to the presence of superconducting clusters (-100 nm) at the surface of Bi. In point contacts with deformed and undeformed Bi two different superconducting phases of Bi are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…The reason of their appearance may be associated with the fast decrease of the Andreev-reflection current near eV = ∆ and chargeimbalance processes. Besides, the superconducting clusters situated at the contact area periphery may result such the horns [11]. In some measurements the spectra occur not symmetrical, as it is shown in Figs.…”
mentioning
confidence: 91%
“…The reason of their appearance may be associated with the fast decrease of the Andreev-reflection current near eV = ∆ and chargeimbalance processes. Besides, the superconducting clusters situated at the contact area periphery may result such the horns [11]. In some measurements the spectra occur not symmetrical, as it is shown in Figs.…”
mentioning
confidence: 91%
“…2(c)]. The deviations are either due to the strong coupling effects in lead or the high current densities achieved in our samples (10 9 A͞cm 2 at 10 mV for a 10 V sample) which can lead to partial gap suppression [18]. Figure 3(a) shows the point-contact spectra ͑dR͞dV vs V ͒ for the same Pb-Cu sample both in the normal and the superconducting state.…”
mentioning
confidence: 95%
“…Alternatively, interface superconductivity between a normal material and a TI has also been discovered [20][21][22]. It has been reported that the point contact between a normal metal and Bi, Sb, or Bi 1−x Sb x alloy shows unusual properties that are ascribed to the presence of superconducting clusters [20].…”
mentioning
confidence: 99%
“…It has been reported that the point contact between a normal metal and Bi, Sb, or Bi 1−x Sb x alloy shows unusual properties that are ascribed to the presence of superconducting clusters [20]. This phenomenon was explained as a result of the difference in the contact potential, which generates an electric dipole layer at the junction and turns the semimetal, Bi and Sb, or semiconductor Bi 1−x Sb x into a superconductor [20,21]. However, the role played by the spin-polarized surface states that were recently discovered in Bi 1−x Sb x [23,24] for inducing the observed superconductivity has not been studied.…”
mentioning
confidence: 99%